The Role of the Taqwa Mosque Community Service in Improving the Welfare of the Medan Community - Maimunah Munthe; Arlina; Siti Zahra; Jahrona Harahap; Syahru Romadhan (al-Afkar, Journal For Islamic Studies, 2025)
Community welfare is a condition for the fulfillment of the material, spiritual, and social needs of citizens in order to be able to live a decent life and be able to develop themselves, so that they can carry out their social functions, as one of the supports that are expected to be able to provide welfare to the community includes mosques, where mosques play another equally important role in contributing to the improvement of the community's economic situation and also coaching about about faith and also morals in society. The purpose of writing this journal is to study more deeply about how the efforts made by the BKM of the Taqwa Mosque in overcoming this problem include the Role of the BKM of the Taqwa Mosque in the Welfare of the People of Medan. The research method used is qualitative using a phenomenological approach, then the data collection techniques in this study are observation, interviews and documentation and the analysis techniques used are data reduction, data presentation, and conclusion drawn/verification. The results of the research found by the researcher are that there are several activities carried out by BKM Masjid Taqwa to support welfare for the community, including providing religious education, social and community programs, social assistance, economic empowerment, cleanliness and welfare, and environmental cleanliness, then the problems experienced by BKM Mosque in implementing all programs include missed communication and lack of funds and lack of facilities or infrastructure of the Mosque.